Focal and multifocal diabetic neuropathies Neuropatia diabética focal e multifocal - Gérard Said (Arquivos de Neuro-Psiquiatria)
Diabetic neuropathy is the most common neuropathy in industrialized countries, with a remarkable range of clinical manifestations. The vast majority of the patients with clinical diabetic neuropathy have a distal symmetrical form that progress following a fiber-length dependent pattern, with predominant sensory and autonomic manifestations. This pattern of neuropathy is associated with a progressive distal axonopathy. Patients are exposed to trophic changes in the feet, pains and autonomic disturbances. Less often, diabetic patients may develop focal and multifocal neuropathy that includes cranial nerve involvement, limb and truncal neuropathies. This neuropathic pattern tends to occur after 50 years of age, mostly in patients with longstanding diabetes mellitus. The LDDP does not show any trend to improvement and either relentlessly progresses or remain relatively stable over years. Conversely the focal diabetic neuropathies, which are often associated with inflammatory vasculopathy on nerve biopsies, remain self limited, sometimes after a relapsing course. A neuropatia diabética é a mais predominante das neuropatias nos países industrializados apresentando uma gama variável de manifestações clinicas. A maioria dos pacientes com neuropatia diabética apresenta uma forma simétrica distal que progride para um padrão fibra comprimento dependente com manifestações sensitivas e autonomicas. Este tipo de neuropatia é associado com uma axonopatia distal progressiva. Os pacientes apresentam modificações tróficas nos pés, dores e distúrbios autonômicos. Menos freqüentemente os pacientes diabéticos podem desenvolver neuropatia focal e multifocal que incluem envolvimento de nervos cranianos, tronco e membros inferiores. Este padrão de neuropatia é mais freqüente em pacientes com mais de 50 anos e com longa historia de diabetes. Este tipo de neuropatia fibra-comprimento dependente não apresenta melhora, progride lentamente ou permanece estável por vários anos. As neuropatias focais que são associadas freqüentemente com vasculopatias inflamatórias nas biópsias de nervo, permanecem auto limitadas por vezes com surtos de remissão.